(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
E-Banking is the term used for new age banking system. It is also called as online banking. E Banking uses the internet as the delivery channel by which to conduct banking activity, for example, transferring funds, paying bills, viewing checking and savings account balances, paying mortgages and purchasing financial instruments and certificates of deposits. Online Banking is a result of explored possibility to use internet application in one of the various domains of commerce. It is difficult to infer whether the internet tool has been applied for convenience of bankers or for the customers’ convenience. But ultimately it contributes in increasing the efficiency of the banking operation as well providing more convenience to customers. Thee-banking is believed to facilitate customers transact from one corner of the country to another corner. But the customers carry varied perception about e-banking services based on multiple factors. The present paper explores the impact of education and occupation of a customer in shaping their perception about internet banking in both Public Sector Bank and Private Sector Bank .